GUIDELINES FOR DEVELOPING THE INTERNAL QUALITY ASSURANCE SYSTEM IN EDUCATIONAL INSTITUTIONS OF DISTRICT LEARNING PROMOTION CENTERS UNDER THE ANG THONG PROVINCIAL OFFICE OF LEARNING PROMOTION - Promthong, Nattiya; Ruphan, Pornthep (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed 1) to study the implementation of internal quality assurance in educational institutions under the District Learning Promotion Centers affiliated with the Office of Learning Promotion in Ang Thong Province, and 2) to propose a development approach for an internal quality assurance system appropriate to the context of these institutions. The study employed a mixed-methods design. The quantitative phase included a population of 122 participants comprising school administrators, teachers, and educational personnel. The qualitative phase involved in-depth interviews with 8 key informants, including school administrators and quality assurance coordinators. Research instruments included a questionnaire, which demonstrated a reliability coefficient of 0.97, and an unstructured interview guide. Data were analyzed using mean, standard deviation, and content analysis. The results revealed that 1) the overall implementation of internal quality assurance within the target institutions was at a high level; and 2) the proposed development approach for the internal quality assurance system consisted of 27 practical guidelines categorized into 8 stages: (1) setting institutional education standards (3 guidelines), (2) developing quality improvement and annual action plans (3 guidelines), (3) implementing the educational development plan (4 guidelines), (4) monitoring and evaluating educational quality (4 guidelines), (5) conducting internal evaluations based on educational standards (4 guidelines), (6) preparing the annual self-assessment report (4 guidelines), (7) submitting and disseminating the report to relevant agencies and the public (4 guidelines), and (8) using evaluation results for strategic quality development planning (4 guidelines).